Issues of Gender Representation in Modern Greek Art: The Case of Thaleia Flora-Caravia's Photographic Images and Self-Portraits. Issue 1 (1st March 2019) - Tsourgianni, Despoina
Abstract : There is a recent trend, mainly in the field of historiography but also in art history, toward the exploration of female autobiographical discourse, whether it concerns written (autobiographies, correspondence), painted (self-portraits), or photographic data. On the basis of the highly fruitful gender perspective, this article seeks to present and interpret the numerous photographs of the well-known Greek painter Thaleia Flora-Caravia. These photographic recordings, taken almost exclusively from the painter's unpublished personal archive, are inextricably linked to the artist's self-portraits. This kind of cross-examination allows the reader to become familiar with the mosaic of roles and identities that constitutes the subjectivity of female artists in Greece in the late nineteenth and early twentieth centuries.